Pharmacophylogenetic insights into Scutellaria strigillosa Hemsl.: chloroplast genome and untargeted metabolomics, quantitative analysis and antibacterial analysis - Shen, Jie; Li, Panpan; Chu, Hairong; Li, Yong; Meng, Xiangying; Li, Zhenpeng; Dou, Jiayao; Wang, Wentao; Liu, Chenyang; Xiao, Peigen; He, Chunnian; Yi, Zhengjun (Frontiers in Plant Science, 2024)
Scutellaria strigillosa Hemsl., known for its traditional use in Chinese herbal medicine, is valued for heatclearing and detoxifying, promoting diuresis, reducing swelling, alleviating pain, and preventing miscarriage. Despite its historical use, comprehensive studies on pharmacophylogenetic analysis, including genetic and chemical profiles and the antimicrobial activity of S. strigillosa are still lacking. Understanding these aspects is crucial for fully realizing its therapeutic potential and ensuring sustainable use. This study aims to elucidate these aspects through comparative genomics, metabolomics, and antimicrobial assays with Scutellaria baicalensis Georgi and Scutellaria barbata D. Don.The chloroplast genome of S. strigillosa was assembled, measuring 152,533 bp, and revealing a high degree of conservation, especially in the protein-coding regions, and identified four regions trnK(UUU)-rps16, trnN(GUU)-trnR(ACG), accD-psaI, psbE-petL) of variability that could serve as phylogenetic markers. The phylogenetic analysis revealed a closer genetic relationship of S. strigillosa with S. tuberifera and S. scordifolia than traditionally classified, suggesting a need for taxonomic reevaluation within the genus. UPLC-QTOF-MSUPLC-Q-TOF-MS analysis in negative ion mode was used to explore the chemical diversity among these species, revealing distinct variations in their chemical compositions. S. strigillosa shared a closer chemical profile with S. barbata, aligning with phylogenetic findings. Metabolomic identification through Progenesis QI software resulted in the tentative identification of 112 metabolites, including a substantial number of flavonoids, diterpenoids, iridoid glycosides, phenylethanoid glycosides, and others. HPLC analysis further detailed the concentrations of 12 actives across the species, highlighting the variation in compound content. S. strigillosa shows antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa, similar to S. baicalensis root extracts. This research enhances the understanding of the phylogenetic and phytochemical profiles and the antibacterial activity of S. strigillosa, offering new insights into its medicinal properties. The findings suggest a need for taxonomic reevaluation within the genus and underscore the potential antibacterial activity of S. strigillosa for therapeutic applications. Further studies are encouraged to explore its full medicinal potential and contribute to the sustainable development of Scutellaria species.